"If You Tilt This Game, Will It Explode?": The politics of nuclear display at the New York Hall of Science (1966–1973). (18th February 2020) - Sastre‐Juan, Jaume
Abstract: This article analyzes the politics of nuclear display at the New York Hall of Science in the late 1960s and early 1970s. The Hall of Science, which had its beginnings in the 1964–1965 New York World's Fair, featured hands‐on atomic exhibits for children and was planning a monumental Nuclear Science Center with the full support of the Atomic Energy Commission. The Nuclear Science Center would have been the biggest permanent display on nuclear science and technology in the United States and the Atomarium its most spectacular exhibit. At the Atomarium, visitors would have watched a working nuclear reactor go critical from a spiral‐shaped theater‐in‐the‐round while listening to a demonstrator standing on a transparent plexiglass window located right above the reactor core lecturing on peaceful uses of atomic energy. This article analyzes the Hall of Science as a space in which contemporary tensions between nuclear exceptionalism and nuclear banalization were played out. In particular, the article explores how playful and immersive regimes of display played a political role in modulating nuclear fear at a time when, while promoting a private nuclear energy industry, the Atomic Energy Commission encountered growing resistance to nuclear power plants.